Improving Students' Reading Comprehension by Using Kahoot! A Classroom Action Research at the Tenth Grade of SMA Bani Muhyiddin Tanjungsiang in Academic Year 2020/2021 - Khofifah Lisniyanti; Dody Wahyudi Purnama; Mimin Aminah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2023)
The purpose of this study is to discover the process of using Kahoot! to improve student's reading comprehension, the improvement of students' reading comprehension after teaching with Kahoot!, and how students respond to the Kahoot! application. The researcher employed a classroom action research design (CAR), and data was gathered through the use of a test, questionnaire, and observation sheets. The outcome revealed that there was a positive response after the action was carried out. Following the action, 66,7% of students strongly agreed that Kahoot! could improve reading comprehension and 53,3% agreed that Kahoot! was effective in learning English. Furthermore, the students' mean pre-test score was 64, and 4 (26,7%) were able to pass the KKM. The mean score of post-test 1 was 69,3, and the percentage of students who passed the KKM was 6 (40%). The mean score of post-test 2 was 74,2, and the percentage of students who passed the KKM was 8 (53,3%). The mean score of post-test 3 was 78,3 and the class percentage of students who passed the KKM was 13 (87%). It can be concluded that Kahoot! is a suitable medium for use in high school, particularly for improving students' reading comprehension.